Full 3D Printing of Stretchable Piezoresistive Sensor with Hierarchical Porosity and Multimodulus Architecture. (27th December 2018) - Wang, Ziya; Guan, Xiao; Huang, Huayi; Wang, Haifei; Lin, Waner; Peng, Zhengchun
Abstract: A soft piezoresistive sensor with its unique characteristics, such as human skin, light weight, and multiple functions, yields a variety of possible practical applications to skin‐attachable electronics, human–machine interfaces, and electronic skins. However, conventional filler‐matrix piezoresistive sensors often suffer from unsatisfactory sensitivity or insufficient measurement range, as well as significant cross‐correlation between out‐of‐plane pressure and in‐plane extension. Here, a stretchable piezoresistive sensor (SPS) is realized by combining a hierarchically porous sensing element with a multimodulus device architecture via a full 3D printing process. As a result, the sensor exhibits high sensitivity (5.54 kPa −1 ), large measurement range (from 10 Pa to 800 kPa), limited cross‐correlation, and excellent durability. Meanwhile, benefiting from the porous structure and mechanical mismatch design, which efficiently distributes the stress away from the sensing element, the device experiences only 7% resistance change at 50% stretching. This approach is employed to rapidly program and readily manufacture stylish, all‐in‐one, functional devices for various applications, demonstrating that the technique is promising for customized stretchable electronics. Abstract : A stretchable piezoresistive sensor with high sensitivity, large measurement range, limited cross‐correlation, and excellent durability is developed by combining a multilayered sensing element of hierarchically porous structure with a multi‐modulus device architecture. This work suggests the potential for fabricating stretchable devices and soft electronics by full 3D printing as a generalized and customizable approach.